The British booksellers [large type] : a novel of the Forgotten Blitz - Cambron, Kristy (Thorndike Press Large Print Christian Fiction, 2024)
"Inspired by real accounts of the Forgotten Blitz bombings, The British Booksellers highlights the courage of those whose lives were forever changed by war--and the stories that bind us in the fight for what matters most. A tenant farmer's son had no business daring to dream of a future with an earl's daughter, but that couldn't keep Amos Darby from his secret friendship with Charlotte Terrington...until the reality of the Great War sobered youthful dreams. Now decades later, he bears the brutal scars of battles fought in the trenches and their futures that were stolen away. His return home doesn't come with tender reunions, but with the hollow fulfillment of opening a bookshop on his own and retreating as a recluse within its walls. When the future Earl of Harcourt chose Charlotte to be his wife, she knew she was destined for a loveless match. Though her heart had chosen another long ago, she pledges her future even as her husband goes to war. Twenty-five years later, Charlotte remains a war widow who divides her days between her late husband's declining estate and operating a quaint Coventry bookshop--Eden Books, lovingly named after her grown daughter. And Amos is nothing more than the rival bookseller across the lane. As war with Hitler looms, Eden is determined to preserve her father's legacy. So when an American solicitor arrives threatening a lawsuit that could destroy everything they've worked so hard to preserve, mother and daughter prepare to fight back. But with devastation wrought by the Luftwaffe's local blitz terrorizing the skies, battling bookshops--and lost loves, Amos and Charlotte--must put aside their differences and fight together to help Coventry survive. From deep in the trenches of the Great War to the storied English countryside and the devastating Coventry Blitz of World War II, The British Booksellers explores the unbreakable bonds that unite us through love, loss, and the enduring solace that can be found between the pages of a book"--